Subsidized Renewables’ Adverse Effect on Energy Storages and Carbon Pricing as a Potential Remedy - Liebensteiner, Mario; Haxhimusa, Adhurim; Naumann, Fabian (Renewable and Sustainable Energy Reviews, 2022)
Large-scale energy storage is viewed as a key complementary technology in a power system fed by a large share of intermittent renewable energies (RE). However, subsidies for RE - a well-intended market intervention - may distort price signals, thereby adversely undermining the profitability of energy storages, and thus, adequate investment incentives. This study provides novel causal estimates supporting this notion, using an econometric instrumental-variables framework and data on Austrian pumped storages, operating in the German-Austrian electricity market, characterized by a large share of generously subsidized RE. The findings show that RE significantly depress storage profitability and that further deployment of RE will intensify this effect. This may pose an obstacle against adequate investment in bulk energy storage capacity. Moreover, the results indicate that intensifying carbon pricing would significantly counteract the problem via a market-based price signal. This study contributes to the general debate on the design and effects of environmental regulation and particularly shows that a non-market-based policy for a green technology may adversely affect complementary technologies.<br
Keywords: Carbon pricing; Decarbonization; Energy transformation; Energy storage; Renewable energies